Surgical treatment of injuries in the capsular-ligamentous apparatus on the lateral part of the ankle joint (a review of literature) - Shishka, Igor; Golovakha, Maksim; Krasnoperov, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Treatment of injuries in the capsular-ligamentous apparatus on the lateral part of the ankle joint remains an urgent problem at present. This is owing to a high rate of such injuries, their incomplete diagnosis during an acute period of the injury and a high level of unsatisfactory results of treatment. Despite a significant umber of works, still there is no common opinion concerning recommendations to surgical or conservative treatment depending upon the injury severity, instability degree and time periods since the moment of injuring. The article examines different techniques of surgical treatment for fresh and neglected injuries in the ligamentous apparatus on the lateral part of the ankle joint. Advantages and shortcomings of the main surgical techniques for treating the above injuries, their early and remote results are analysed on the basis of Ukrainian and foreign scientific sources, as well as indications for using each of them in the presence of fresh and neglected injuries in the ligamentous apparatus on the lateral part of the ankle joint are clearly grounded.